2020
DOI: 10.1039/d0sc04754f
|View full text |Cite
|
Sign up to set email alerts
|

Identifying reactive intermediates by mass spectrometry

Abstract: Development of new reactions requires finding and understanding of novel reaction pathways. In challenging reactions such as C-H activations, these pathways often involve highly reactive intermediates which are the key...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 70 publications
0
68
0
3
Order By: Relevance
“…The challenge of identifying and resolving occluded species is non-trivial to the study of dynamic libraries of self-assembling species in solution ( Figure 3 ) ( Misuraca et al, 2014 ). Mass spectrometry gives ready access to real time analysis of dynamic systems on a millisecond timescale ( Schalley and Springer, 2009 ; Hudgens et al, 2011 ; Pettibone and Hudgens, 2012 ; Olivares et al, 2014 ; Yunker et al, 2014 ; Ligare et al, 2017a ; Ligare et al, 2017b ; Ujma et al, 2017 ; Schnell et al, 2019 ; Mehara and Roithová, 2020 ; Zelenka and Roithová, 2020 ). The difficulties of occluded isobaric and isomeric species can be overcome by adding a filter for shape and size, in addition to m/z , namely, an ion-mobility spectrometer (IMS) ( Ujma et al, 2017 ; Polewski et al, 2021 ).…”
Section: Self-assembly and Coordination Driven Self-assemblymentioning
confidence: 99%
“…The challenge of identifying and resolving occluded species is non-trivial to the study of dynamic libraries of self-assembling species in solution ( Figure 3 ) ( Misuraca et al, 2014 ). Mass spectrometry gives ready access to real time analysis of dynamic systems on a millisecond timescale ( Schalley and Springer, 2009 ; Hudgens et al, 2011 ; Pettibone and Hudgens, 2012 ; Olivares et al, 2014 ; Yunker et al, 2014 ; Ligare et al, 2017a ; Ligare et al, 2017b ; Ujma et al, 2017 ; Schnell et al, 2019 ; Mehara and Roithová, 2020 ; Zelenka and Roithová, 2020 ). The difficulties of occluded isobaric and isomeric species can be overcome by adding a filter for shape and size, in addition to m/z , namely, an ion-mobility spectrometer (IMS) ( Ujma et al, 2017 ; Polewski et al, 2021 ).…”
Section: Self-assembly and Coordination Driven Self-assemblymentioning
confidence: 99%
“…7,8 This is despite the fact that it has been widely used to investigate non-photochemical reactions. [9][10][11] Very recently, a number of on-line photolysis set ups have been demonstrated that dramatically enhance the potential of mass spectrometry as a tool for monitoring photochemical reactions. [12][13][14] In this paper, we describe the application of an instrument that combines on-line photolysis with electrospray ionization mass spectrometry detection and laser-interfaced mass spectrometry (LIMS) to study the photodissociation of CO from metal carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…| RSC Adv., 2021,11,[19500][19501][19502][19503][19504][19505][19506][19507] © 2021 The Author(s). Published by the Royal Society of Chemistry…”
mentioning
confidence: 99%
“…This experimental approach which characterizes the gas-and solution-phase behavior of a chosen system provides a "one-pot" tool for approaching the understanding photochemistry. The technique builds on other recent experiments which have employed on-line photolysis, with subsequent mass spectrometric detection [16][17][18][19][20]. The benefit of this approach is that the solution-phase measurements probe a more "real-world" environment for the riboflavin vitamin (e.g., when it is in milk or within a cosmetic formulation), while the gas-phase measurements aid the understanding of the solution-phase photochemical mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of this approach is that the solution-phase measurements probe a more "real-world" environment for the riboflavin vitamin (e.g., when it is in milk or within a cosmetic formulation), while the gas-phase measurements aid the understanding of the solution-phase photochemical mechanisms. The solution-phase environment is potentially much more complex, since direct photoproducts can undergo secondary reactions and will be subject to environmental factors, i.e., pH, solvent, and aggregation [5,[16][17][18][19][20]. This two-step method provides a new approach that could be widely applied to characterize the photochemical breakdown of food, beauty, and pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%